A NEW TECHNIQUE TO SECURE DATA USING COLORS AND WHOLE NUMBERS - PROF. N. J. GHATGE; PROF. U. A. PATIL (International Journal of Innovations in Engineering Research and Technology, 2021)
Now day’s data security is the majorissue. Confidentiality, Integrity, Non-repudiation is the main components of data security. The widespread strategy for the security of transmitted data is cryptography. In thiswork, a prime approach for security and encryption of data has been examined.In this, colors are used as a passwords involving key and whole numbers are utilizedfor the encryption purpose. The secure data transmission is given by utilizing set of three key point with a crucial security component acted by the colors along these lines giving authentication.